Effect of water pollution by nickel on hepatic enzymes and oxidative enzymes in Cyprinus carpio (common carp) - Hammoud, Haitham Ali; Aldhamin, Ahmed Saad (Brawijaya University, 2024)
Nickel (Ni) is considered a toxic heavy metal that causes serious diseases in humans and animals. Therefore, this study was conducted on common carp, which is considered an essential food item for humans. This study was designed to investigate the effect of nickel on the hepatic and antioxidant enzymes of Cyprinus carpio after 3 and 6 weeks of exposure to water contaminated with Ni. C. carpio fingerlings were purchased from a neighboring fish hatchery. The morphometric characteristics of the experimental fish were documented. All fish were stocked, regardless of gender. The fish were exposed to different concentrations (20, 40, 60, 80, and 100 mg/L) to obtain the LC50 for Ni during 96 hours, and the median lethal concentration of Ni was 80 mg/L through 96 hours. The fish were exposed to two safe concentrations, 1 ppm and 5 ppm. The results after 3 and 6 weeks were as follows: When compared to the control groups, all treated groups had significantly higher levels of liver function parameters (ALT and AST). Malondialdehyde (MDA) and catalase activity measurement (CAT) enzyme levels were considerably higher in all treated groups after 3 and 6 weeks as compared to control groups. These changes are trustworthy indications of the cellular and humoral immune responses in C. carpio.